The formation and development of the theory of individual style in world linguistics - Xaydarov, Dovranjon Turgunovich (The Lingua Spectrum, 2026)
This article examines the theoretical foundations of the concept of individual style and its role in stylistics, text linguistics, and linguopoetics. The essence and content of the category of style are analyzed through the views of prominent linguists, and the stages of the formation and development of the theory of individual style are discussed. The study summarizes scholarly approaches from ancient thinkers to contemporary linguistic researchers. Particular attention is paid to the relationship between individual style and the author’s linguistic personality, aesthetic thinking, communicative strategy, and national-cultural worldview.